FOOD AND HEALTH IN PORTUGUESE CISTERCIAN MONASTERIES - Rodarte, Vitoria Maria [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias Humanas & Sociais, 2020)
Throughout history, food has fulfilled several roles, but when we analyze more closely the Christian influence on eating habits, it is possible to verify that food, in addition to the basic conditions of survival, were used to restore the health of the sick, especially in monastic houses of the Low Middle Ages and, after the IV Lateran Council, for the belief in the transubstantiation that symbolically transformed bread and wine into the body and blood of Christ for spiritual healing. In this work, we are interested in interrogating the importance of food within a set of prescriptions for the care of body and soul, analyzing the reasons that led this aspect to be written in important works of the Cistercian Order, translated and disseminated in the Portuguese monastery of Alcobaca.
Keywords: Food; Cistercian; Alcobaca